Age, hypertension, and lacunar stroke are the major determinants of the severity of age-related white matter changes: the LADIS (Leukoaraiosis and Disability in the Elderly) Study - Basile, Anna Maria; Pantoni, Leonardo; Pracucci, Giovanni; Asplund, Kjell; Chabriat, Hugues; Erkinjuntti, Timo; Fazekas, Franz; Ferro, José M.; Hennerici, Michael G.; O'Brien, John; Scheltens, Philip; Visser, Marieke C.; et al. (Cerebrovascular diseases, 2006)
BACKGROUND: Age-related white matter changes (ARWMC), seen on neuroimaging with high frequency in older people, are thought to be consequent to the effect of vascular risk factors and vascular diseases including hypertension and stroke. Among the proofs conventionally required for a factor to be considered a risk factor for a definite pathology, there is the demonstration of a trend in risk exposure related to disease severity. We sought whether such a trend existed in the association of vascular risk factors or comorbidities with the severity of ARWMC aiming particularly at further elucidating the relative roles of hypertension and stroke in this regard. - METHODS: The LADIS (Leukoaraiosis and Disability) Study is evaluating the role of ARWMC as an independent determinant of the transition to disability in the elderly. Six hundred and thirty-nine nondisabled subjects (mean age 74.1+/-5.0, M/F: 288/351) with ARWMC of different severity grades on MRI (mild, moderate, or severe according to the Fazekas scale) were assessed at baseline for demographics, vascular risk factors, and comorbidities, and are being followed up for 3 years. - RESULTS: Age, frequency of hypertension and history of stroke increased along with increasing ARWMC severity independently of other factors. For hypertension, however, this occurred only in subjects without a stroke history, while for stroke history, it mainly depended on lacunar stroke. The amount of cigarettes smoked and the interaction between hypercholesterolemia and smoking predicted only the most severe ARWMC grade. - CONCLUSIONS: The LADIS Study confirms that age, hypertension and lacunar strokes are the major determinants of ARWMC. Smoking and hypercholesterolemia provide additional risk.
Gesehen am 09.05.2022